Answer :

Let f(x) = x3 + 3x2 – px + 24.

By factor theorem,


x + 3 = 0;x = – 3


(x + 3) is a factor of f(x)


So, f(– 3) = 0.


f(– 3) = (– 3)3 – 3(– 3)2 – p(– 3) + 24 = 0


= >27 – 27 + 3p + 24 = 0


= > – 59 + 24 + 3p = 0


3p – 30 = 0


p = 30/3


p = 10


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

One of the factorTamilnadu Board Math Term-I

The root of polynTamilnadu Board Math Term-I

The root of polynTamilnadu Board Math Term-I

The polynomial 4xTamilnadu Board Math Term-I

The degree of polTamilnadu Board Math Term-I

If (ax – b) is a Tamilnadu Board Math Term-I

The coefficient oTamilnadu Board Math Term-I

One of the factorTamilnadu Board Math Term-I

Determine whetherTamilnadu Board Math Term-I

Using factor theoTamilnadu Board Math Term-I